VASCULAR EPIPHYTES IN DRY OAK FORESTS SHOW RESILIENCE TO ANTHROPOGENIC DISTURBANCE, CORDILLERA ORIENTAL, COLOMBIA - Higuera Diego; Wolf Jan (Caldasia)
We compared the richness and biomass of vascular epiphytes in six seasonally semideciduousoak (Quercus humboldtii) forest fragments of varying structure, using theSVERA protocol. Bromeliads dominated epiphytic vegetation in terms of richness,10 out of a total of 17 species, and biomass (98%), but overall epiphyte community development was poor in comparison with neotropical wet mountain forests. Epiphyte richness and biomass was similar in all fragments, except one bottom-valley fragment,despite large differences in anthropogenic-induced forest structure. We hypothesizethat epiphyte resilience to disturbance in these dry oak forest fragments is due totolerance of the local epiphyte species to desiccation, overriding micro-climaticdifferences between forest fragments of different structure.